Perbedaan Somatotype Atlet Futsal Vamos FC Mataram dan Atlet Basket Bima Perkasa Jogja - Maulana, Wahyu Gading (Fakultas Ilmu Olahraga, Universitas Negeri Surabaya, 2019)
ABSTRACTThis study aims to determine the differences in the somatotypes of futsal and basketball athletes. This research is an analytical observational study with cross-sectional approach. Research subjects were 30 professional futsal and basketball athletes. Determination of somatotype using the Heath-Carter method using the antropometric measurements. Data analysis to determine the differences in the somatotypes of futsal and basketball athletes using the independent sample T-test. The result of the independent T-test to find out the difference between futsal and basketball athletes with Î± determained at 0.05 obtained a significance level of 0.047 in mesomorph athletes which signifies a significant correlation between futsal and basketball athletes somatotypes. There are differences in somatotypes of futsal and basketball athletes with mesomorph types Keyword: Basketball, Futsal, Somatotype